Conceptualization Of The Protection Of Human Rights For Victims Of The Crime Of Trafficking In Indonesia - Hilman, Zihan Maulida Mulyani; Prasetyoningsih, Nanik (Faculty of Law, Universitas Pekalongan, 2024)
The criminal act of human trafficking has caused suffering because it is a crime that violates human dignity, and so the crime is included in the category of serious crimes. The aim of this research is: This research aims to find out and examine the concept of the criminal act of trafficking in persons in Indonesia, to find out and examine the weaknesses in the arrangements for protecting the human rights of victims of the crime of trafficking in persons in Indonesia, and to find out and examine the conceptualization of the protection of the human rights of victims. Criminal act of human trafficking in Indonesia. This research is a type of normative-empirical legal research that examines the legal problem of human trafficking with a multidimensional approach. The research results show that protecting human rights for victims of human trafficking in Indonesia involves various parties and requires a holistic approach. Despite significant efforts, protection limitations remain, including service, compensation and return costs. Further efforts are needed to address these challenges and ensure maximum protection for victims while continuing to evaluate and monitor for continuous improvement.